Chronic Tinnitus following Electroconvulsive Therapy - Robert L. Folmer; Yongbing Shi; Sarah Theodoroff (Case Reports in Psychiatry)
A 43-year-old female with a 27-year history of obsessive-compulsive disorder and major depression had previously been treated with psychotherapy, antidepressant, and antipsychotic medications. Because these treatments were minimally effective and because the frequency and duration of her depressive episodes continued to increase, the patient was scheduled to undergo a series of electroconvulsive therapy (ECT) procedures. The patient received four ECT treatments during one month. Stimulating current was delivered to the right frontotemporal region of the head. Electroencephalographic seizures occurred during each of the ECT procedures. After the patient recovered from anesthesia, she complained of headaches, muscle pain, amnesia, and, after the fourth ECT, she reported a ringing sound in her right ear. Audiometric testing the day after the fourth ECT revealed a slight increase in threshold for 8000 Hz tones in her right ear. It is likely that current delivered during the fourth ECT treatment triggered the perception of tinnitus for this patient. The unique organization of this patient's central nervous and auditory systems combined with her particular pharmacological history might have predisposed her to developing tinnitus.